2013
DOI: 10.21273/jashs.138.4.310
|View full text |Cite
|
Sign up to set email alerts
|

Haploid Induction in Hull-less Seed Pumpkin through Parthenogenesis Induced by X-ray-irradiated Pollen

Abstract: Production of hull-less seeds of styrian oil pumpkin (Cucurbita pepo ssp. pepo var. styriaca) is increasing as a result of demand for aromatic seed oil and for other uses. Hybrid cultivars have recently been released but a method for haploid induction has not been established. We focused on the development of a parthenogenetic haploid induction protocol based on pollination with pollen irradiated with X-ray radiation at 0,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 26 publications
(38 reference statements)
1
19
0
7
Order By: Relevance
“…Related studies show that the number of seeds generated by pollination with irradiated pollen is a function of genotype (Nasertorabi et al, 2012), while the frequency of haploids generated using irradiated pollen is a function of the recipient female parent and the pollen donor (Koṧmrlj et al, 2013). Also, haploid production from the same genotype is not consistent across different pollination events with irradiated pollen (Koṧmrlj et al, 2013). Our study consisted of only one cassava genotype, Nase 14.…”
Section: Samplementioning
confidence: 88%
See 3 more Smart Citations
“…Related studies show that the number of seeds generated by pollination with irradiated pollen is a function of genotype (Nasertorabi et al, 2012), while the frequency of haploids generated using irradiated pollen is a function of the recipient female parent and the pollen donor (Koṧmrlj et al, 2013). Also, haploid production from the same genotype is not consistent across different pollination events with irradiated pollen (Koṧmrlj et al, 2013). Our study consisted of only one cassava genotype, Nase 14.…”
Section: Samplementioning
confidence: 88%
“…These results annul an earlier hypothesis by Viera et al (2012) claiming the presence of a specific substance found in the stigma but not in the medium that induces pollen germination, which opens up opportunities to study the impact of irradiation in cassava. The effects of ionizing radiation on pollen germination have been studied in a number of plants (Visser and Oost, 1981;Pooler and Scorza, 1997;Musial and Pryzwara, 1998;Yue and Zou, 2012;Koṧmrlj et al, 2013). These studies generally concluded that irradiation results in a reduction of pollen germination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fruit set is lower when pollination is performed using irradiated pollen [3]. The number of female flowers that develop into a fruit can range between 10-25% in melon [3], 20-25% in pumpkin [8] or 50% in cucumber [9]. The initial number of parthenogenetic embryos is crucial to have enough plant material during the whole process.…”
Section: Pollination With Irradiated Pollen and Fruit Setmentioning
confidence: 99%